2020
DOI: 10.1002/ece3.6307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tower base painting on willow ptarmigan collision rates with wind turbines

Abstract: Renewable energy production is regarded essential to meet the increasing energy demands while also reducing emissions of CO 2 necessary to reduce risk of global warming (IEA, 2016;IPCC, 2014). In recent years, the production of wind energy has increased worldwide and is still developing fast (IRENA, 2017).Although regarded as a low-carbon energy option, wind energy production may cause negative environmental effects, especially on wildlife (Tabassum-Abbasi, 2014). At onshore wind-power plants, birds and bats a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
0
17
0
1
Order By: Relevance
“…This study presents the outcomes of the first dedicated in situ experiment extensively testing the efficacy of passive markings to reduce collision mortality at wind turbines (but see Stokke et al., 2020). The annual fatality rate was significantly reduced at the treated turbines by over 70%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study presents the outcomes of the first dedicated in situ experiment extensively testing the efficacy of passive markings to reduce collision mortality at wind turbines (but see Stokke et al., 2020). The annual fatality rate was significantly reduced at the treated turbines by over 70%.…”
Section: Discussionmentioning
confidence: 99%
“…Bird fatalities within the entire wind‐power plant included a suite of species with varying susceptibility to collision with the wind turbines. Of these species, willow ptarmigan (excluded from this study as they were expected to collide with the turbine tower, see Stokke et al., 2020) and white‐tailed eagle had the highest number of recorded carcasses. Before the experiment, six white‐tailed eagles were found dead at to‐be‐painted turbines but after painting none.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also likely that some species, based simply on life history, primarily collide with turbine poles and rarely collide with blades themselves [6,20,93]. Carcasses of low-flying upland game birds, which are unlikely to ever fly into the rotor zone, have been routinely found during carcass searches [34,[94][95][96][97] and Stokke et al [98] found substantial evidence that willow ptarmigan (Lagopus lagopus) frequently collide with turbine poles in Norway. Further, the distance distribution for willow ptarmigan mirrored ours, showing a high peak directly next to the turbine pole (Fig 3) [98].…”
Section: Differences Between Birds and Batsmentioning
confidence: 99%